2022
DOI: 10.1186/s12939-022-01712-6
|View full text |Cite
|
Sign up to set email alerts
|

Disease-specific distress healthcare financing and catastrophic out-of-pocket expenditure for hospitalization in Bangladesh

Abstract: Background Financial risk protection and equity are two fundamental components of the global commitment to achieve Universal Health Coverage (UHC), which mandates health system reform based on population needs, disease incidence, and economic burden to ensure that everyone has access to health services without any financial hardship. We estimated disease-specific incidences of catastrophic out-of-pocket health expenditure and distress financing to investigate progress toward UHC financial risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…On the contrary, families where a female is the breadwinner face higher CHE [ 4 , 20 , 22 , 50 ]. Studies from China, Pakistan, Iran, and Vietnam revealed that families with elderly (aged 65+) have higher CHE incidence [ 4 , 32 , 33 , 47 , 52 ]. However, a study from Nigeria identified having the elderly as a weak predictor of CHE [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, families where a female is the breadwinner face higher CHE [ 4 , 20 , 22 , 50 ]. Studies from China, Pakistan, Iran, and Vietnam revealed that families with elderly (aged 65+) have higher CHE incidence [ 4 , 32 , 33 , 47 , 52 ]. However, a study from Nigeria identified having the elderly as a weak predictor of CHE [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among lower risk children, risk stratification may limit the use of unnecessary interventions thus reducing nosocomial infection, 19 antimicrobial resistance, and catastrophic household medical expenses. 20 …”
Section: Discussionmentioning
confidence: 99%
“…On average, Bangladeshi citizens must pay 63.3% of their total treatment costs out of their own pockets [72] . A study found that about 26% of households incurred catastrophic health expenditures in Bangladesh [73] . The problem is simply worse in the CHT region because of its geographical structure which results in substantial transportation costs, which pose a financial burden for the vulnerable older population.…”
Section: Discussionmentioning
confidence: 99%